2020
DOI: 10.1007/s00213-020-05641-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced attentional capture by reward following an acute dose of alcohol

Abstract: Rationale Previous research has shown that physically-salient and reward-related distractors can automatically capture attention and eye-gaze in a visual search task, even though participants are motivated to ignore these stimuli. Objectives To examine whether an acute, low dose of alcohol would influence involuntary attentional capture by stimuli signalling reward. Methods Participants were assigned to the alcohol or placebo group before completing a visualsearch task. Successful identification of the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Another limitation is that we did not collect information about acute alcohol use at baseline which may have influenced cognitive performance. While it is unlikely that acute alcohol use contributed to the current findings (because acute alcohol use reduces VMAC (Watson, Pearson, & Le Pelley, 2020) it may have added unnecessary variance to the data. A related limitation is that we did not measure or control for problematic alcohol use which has been shown to predict temporary abstinence outcomes in past research (de Visser & Nicholls, 2020).…”
Section: Discussionmentioning
confidence: 83%
“…Another limitation is that we did not collect information about acute alcohol use at baseline which may have influenced cognitive performance. While it is unlikely that acute alcohol use contributed to the current findings (because acute alcohol use reduces VMAC (Watson, Pearson, & Le Pelley, 2020) it may have added unnecessary variance to the data. A related limitation is that we did not measure or control for problematic alcohol use which has been shown to predict temporary abstinence outcomes in past research (de Visser & Nicholls, 2020).…”
Section: Discussionmentioning
confidence: 83%
“…This automatic prioritization of stimuli that provide information about motivationally significant events extends beyond threat. A substantial body of existing research has also demonstrated automatic attentional capture by signals of reward (for reviews, see: Anderson, 2016; Le Pelley et al, 2016; Rusz et al, 2020; see also Watson et al, 2020). Taken together, the implication is that effects of associative learning on attention are driven by the motivational salience of the predicted outcome (i.e., the extent to which that outcome will motivate behavior) rather than the valence of the outcome (whether it is appetitive or aversive: see Watson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Primary analyses for both single-distractor and choice trials were conducted on the percentage of trials in which gaze was recorded within the distractor ROI(s). As in previously reported analysis protocols (Le Pelley et al, 2015; Pearson et al, 2015, 2016; Watson, Pearson, & Le Pelley, 2020), data from the first two trials and the first two trials after each break were discarded to minimize the potential for artefacts as a result of participants (re)engaging with the task. Timeouts (1.8% of all trials) were also discarded.…”
Section: Methodsmentioning
confidence: 99%